Factors Affecting Production, Consumption and Work Expended Sugarcane farmers in Lampung Province - Fitriani Fitriani; Sutarni Sutarni; Luluk Irawati (Politeknik Negeri Lampung, 2013)
Lampung Province is a centre of sugarcane production. Mostly, sugarcane plantation is developed by corporate in Lampung. Only 15% sugarcane plantation produced by farmer in rural. Unfortunately, sugarcane farmers in Lampung still dominated by small scale plantation. They still face clasical problem in providing input production caused by the limited capital. The research aims to analysis sugarcane production, labor allocation, and consumption pattern. The research conducted on July to November 2012 located in Bandar Agung village, Muara Sungkai subdistrict, North Lampung regency, Lampung Province. Thirty respondents was choosen purposively. Analysis data arranged as econometric model with partial equilibrium. Based on result and discussion performed that sugarcane production model significanly explained by land, urea, SP36 fertilier, labor, and land dummy variable. Labor allocation in sugarcane farming determined by household total income, member of family labor, sugarcane land area, and food consumption. Sugarcane farmer on food consumption influenced by household total income, member of family, and saving. Key words: sugarcane, production, labor allocation, consumption, food